2017
DOI: 10.1109/jsen.2017.2659780
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and Robust Detection of Freezing of Gait Episodes With Wearable Electronic Devices

Abstract: A wearable wireless sensing system for assisting 1 patients affected by Parkinson's disease is proposed. It uses inte-2 grated micro-electro-mechanical inertial sensors able to recognize 3 the episodes of involuntary gait freezing. The system operates in 4 real time and is designed for outdoor and indoor applications. 5 Standard tests were performed on a noticeable number of 6 patients and healthy persons and the algorithm demonstrated 7 its reliability and robustness respect to individual specific gait 8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…The time domain analysis has the great advantage of performing a lower number of calculations, which turns into smaller power consumption and longer battery life. So far, very few studies with the pure time domain approach have been reported and among them, the work by Kwon et al ( 25 ), which was based on the use of the root mean square of the accelerometer signal, and our previous work ( 52 ), which was based on the fusion of raw accelerometers and gyroscope signals. Both time domain approaches detected FOG episodes through a threshold method ( 25 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The time domain analysis has the great advantage of performing a lower number of calculations, which turns into smaller power consumption and longer battery life. So far, very few studies with the pure time domain approach have been reported and among them, the work by Kwon et al ( 25 ), which was based on the use of the root mean square of the accelerometer signal, and our previous work ( 52 ), which was based on the fusion of raw accelerometers and gyroscope signals. Both time domain approaches detected FOG episodes through a threshold method ( 25 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, very few studies with the pure time domain approach have been reported and among them, the work by Kwon et al ( 25 ), which was based on the use of the root mean square of the accelerometer signal, and our previous work ( 52 ), which was based on the fusion of raw accelerometers and gyroscope signals. Both time domain approaches detected FOG episodes through a threshold method ( 25 , 52 ). Kwon et al ( 25 ) studied 20 patients with PD, obtaining a SE and a SP over 85%, whereas Kita et al ( 52 ) studied 16 patients with PD, obtaining a SE and a SP over 94%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this frame, wearables devices and body sensor networks are attracting most attention for the treatment of chronic diseases of elderly, who need monitoring of the symptoms and adjustment of pharmacological therapies [1,2].…”
Section: Introductionmentioning
confidence: 99%